EFFECT OF THE USE OF ENSILED APPLE BAGASSE ON PERFORMANCE AND RUMINAL FERMENTATION IN LAMBS - IGNACIO MEJIA HARO; Maritza De Alba González; José Manuel Martínez Mireles; Carlos Fernando Arechiga Flores (Journal of Animal and Plant Sciences, 2023)
This study evaluates the effects of ensiled apple bagasse (EAB) in lamb diets on their performance and ruminal fermentation. Eighteen Dorper-Kathadin weaned, intact, male lambs (initial body weight 23.070 ± 2.207 kg) were randomly assigned to receive one of three treatments for 77 days: T1 (control diet without EAB); T2 (diet with 20% EAB); and T3 (diet with 40% EAB). The diets were formulated to be isonitrogenous, and the diets’ nutrient compositions was determined. Daily feed intake was measured, lambs were weighed monthly, and the feed conversion ratio was calculated at the end of the experiment. VFAs and N-NH3 production and the pH of ruminal fluid were determined. The data were analyzed by analysis of variance using SAS, and the means were compared using the Tukey test (P < 0.05). Daily weight gain was not different among treatments (P > 0.05). The feed conversion ratio was lower for T1 and T2 than T3 in the growing period (P < 0.05) but was not different in the finishing period. VFA production was higher in lambs fed T3 than those fed T1 and T2 (P < 0.05). No differences were observed in the proportion of acetic acid and N-NH3 concentration. The propionic acid production was higher for T1 compared to T2 and T3, and butyric acid was higher for T3 than T1. The results show that EAB can be used as an alternative for lamb diets to reduce production costs.
Keywords: Sheep; apple pomace; weight gain.